Stabilizing an attractive Bose-Einstein condensate by driving a surface collective mode - Pattanayak, Arjendu K.; Gammal, Arnaldo [UNESP]; Sackett, Charles A.; Hulet, Randall G. (American Physical Society (APS), 2001)
Bose-Einstein condensates with attractive interatomic interactions undergo collective collapse beyond a critical number. We show theoretically that if the low-lying collective modes of the condensate are excited, the radial breathing mode further destabilizes the condensate. Remarkably, excitation of the quadrupolar surface mode causes the condensate to become more stable, imparting quasiangular momentum to it. A significantly larger number of atoms may then occupy the condensate. Efforts are under way for the experimental realization of these effects. ©2001 The American Physical Society.